Zinc determination in samples fish by GFAAS using acid digestion in an ultrasound bath - de Lima, Paula Monteiro [UNESP]; Cavecci, Bruna [UNESP]; Roldan, Paulo dos Santos; Braga, Camila Pereira [UNESP]; Padilha, Cilene do Carmo Federici [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Padilha, Pedro de Magalhães [UNESP] (Springer Nature, 2016)
The aim of this paper was to determine the zinc concentrations in muscle samples of Nile tilapia (Oreochromis niloticus) produced in aquaculture and fed diets containing inorganic and organic zinc sources. In the sample preparation step, the samples were lyophilized and ground cryogenically to produce particles smaller than 60 µm. The zinc extraction was conducted by acid mineralization using concentrated nitric acid and hydrogen peroxide in a thermostatically controlled ultrasonic batch reactor. The zinc determinations were performed by Graphite Furnace Atomic Absorption Spectrometry at a drying temperature of 90–250 °C, pyrolysis temperature of 1400 °C, atomization temperature of 2400 °C, and cleaning temperature of 2800 °C. Niobium nitrate was used as a chemical modifier co-injected with the samples, and tungsten was employed as a permanent modifier. Among the muscle tissue samples of Nile tilapia that were analyzed, zinc concentrations were determined in the range of 3.70–19.00 mg kg−1 (LOD 0.012 µg L−1 and LOQ 0.041 µg L−1). The accuracy and precision of the proposed method of zinc determination was validated using the DORM-certified standard Fish Protein 4 NRC.
Keywords: Chemical modifier; Fish; GFAAS; Zinc